Promoting 'Healthy Childhoods' and Keeping Children 'At Home': Beninese Anti‐Trafficking Policy in Times of Neoliberalism. (18th April 2013) - Howard, Neil
Abstract This article offers the first examination of its kind of the content and nature of anti‐trafficking policy as it is pursued in Benin. The article draws on data gathered from policy and project documents and from interviews and participant observation with actors integral to the constitution of policy in (and with influence over) the Beninese anti‐trafficking community. It attempts to bridge the oft‐lamented gap between page and practice by conducting analysis not only of the representation of policy in text, but also of its lived manifestations in processes, interactions and structures. It argues that the various different actors that comprise Benin's anti‐trafficking pantheon seek to accomplish one fundamental goal – to protect children from trafficking – through two overarching strategies – the promotion of 'healthy' childhoods and the pre‐emptive prevention of child movement. The article examines each of the main strands of policy and concludes by offering a Foucauldian analysis of their operation. It thus fills a major gap in the academic understanding of anti‐trafficking policy in the Beninese context.